Semiotics Applied to Human-Robot Interaction in Welding Processes - Baldez, Patrick; Schot, Mateus; Espíndola, Danubia; Botelho, Silvia; Guterres, Bruna; Soares, Luciane (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
Teleoperation of robotic systems requires efficient and effective human-robot interactions. The present work presents the development of a semiotic-based human-robot interaction interface through the identification of the signs classes presented in the original interface of the robotic welding equipment BUG-O MDS-1005. Among the hardware equipments necessary to construct the proposed interface there are a Raspberry Pi 3 with a 7 inch touchscreen display, an Odroid XU4 and an Arduino Uno. In order to enable users to make use of an intuitive system that meets industry standards, HumanRobot Interaction (HRI) technologies are used. Furthermore, the proposed human-robot interaction interface provides new functionalities enhancing not only the system usability but also the operator productivity during welding processes.